Regulation of immune cell metabolism by cancer cell oncogenic mutations. Issue 2 (25th February 2020) - Madi, Alaa; Cui, Guoliang
Abstract : In noncancerous tissues, neighboring cells coexist in metabolic harmony. This metabolic harmony is disrupted in cancerous tissues, often accompanied by genetic mutations. Tumor cells fundamentally change the metabolite profiles in the tumor microenvironment to favor their own growth. In this review, we will discuss several examples in which genetic mutations reprogram tumor cell metabolic pathways, leading to the consumption of essential nutrients in the tumor microenvironment, production of toxic byproducts, and suppression of antitumor immune cell metabolic fitness and tumor‐killing function. Finally, we will briefly discuss how immune checkpoint blockade overcomes the metabolic suppression of tumor‐infiltrating immune cells.